Porcine reproductive respiratory syndrome: presentation in time and effect on reproductive parameters and productive - Velásquez Vergara, Carlomagno (2017)
The aim of this study was to evaluate the presentation of Porcine Respiratory Reproductive Syndrome (PRRS) across the years and determine its effect on productive and reproductive parameters. The productive performance of 210 Camborough 22 sows that farrowed from 2013 to 2015 in a pig farm in Lima, Peru was evaluated. The characteristics under analysis were: mean litter size per week (NT), total piglets born alive (NV), total piglets born dead (NM), liveweight of piglets born (PVLN), total weaned piglets (LD), live weight of weaned piglets (PVLD), mortality of piglets at weaning (MLD), live weight of piglets at 70 days (PVL70) and mortality of piglets at 70 days (ML70). The increase of NM above the normal limits of control charts lasted 13 weeks. It was evident from week 95 (fourth week in October 2014) and continued through week 108 (second week in February 2015). In the year of presentation of PRRS, the NM, PVLN and ML70 increased by 2.3 times, 6.89% and 13 times, respectively (p<0.05), while the NT, NV, LD, MLD and PVL70 decreased by 16.4, 22.0, 20.5, 44.6 and 11.6%, respectively (p<0.05) This reduced incomes lower productivity per sow/year to 35.6%. The PRRS affected the main reproductive and productive parameters to 70 days of age causing economic losses.